miR145 Regulates the Proliferation and Apoptosis of Rat Vascular Endothelial Cells under Hyperglycemia by Targeting the ANGPT2 Gene and Involving the NFκB Signaling Pathway - Zhang W; Tang XH; Zhang JJ; He Q (Diabetes, Metabolic Syndrome and Obesity, 2020)
Wen Zhang,1 Xin-Hua Tang,2 Jin-Juan Zhang,3 Quan He4 1Clinical Medical Research Center and Yunnan Provincial Key Laboratory of Clinical Virology (2018DG010), First People’s Hospital of Yunnan Province, Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan 650032, People’s Republic of China; 2Center of Genetic Diagnosis, First People’s Hospital of Yunnan Province, Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan 650032, People’s Republic of China; 3Kunming Institute of Zoology, Chinese Academy of Science (CAS), Kunming, Yunnan, 650223, People’s Republic of China; 4Emergency Department, First People’s Hospital of Yunnan Province, Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, 650032, People’s Republic of ChinaCorrespondence: Quan HeEmergency Department, First People’s Hospital of Yunnan Province, Affiliated Hospital of Kunming University of Science and Technology, 157 Jinbi Road, Xishan District, Kunming 650032, Yunnan Province, People’s Republic of ChinaTel +86 871 6363 9921Fax +86 871 6362 7731Email hequan2009@yeah.netPurpose: A majority of diabetes mellitus patients with disturbances of glucose metabolism present with vascular complications. This study aimed to explore regulatory mechanisms of miR145 and its potential target gene ANGPT2 on diabetic vasculopathy under hyperglycemia.Methods: Based on the fact that miR145 is detected in rat aortic endothelial cells (RAECs) under hyperglycemia, RAECs were transfected with miR145 mimics/inhibitor for further confirmation. RAEC proliferation was detected with CCK8 assays, and cell apoptosis and CD34+-cell population with annexinV–PI staining and anti-CD34FITC on flow cytometry, respectively. Then, qPCR and Western blot were applied to detect mRNA and protein expression of ANGPT2 and involved pathway factor NFκB p65. Subsequently, dual luciferase–reporter gene analysis was utilized to verify whether miR145 acted directly upon the 3ʹUTR of ANGPT2 mRNA.Results: The ANGPT2 gene was confirmed to be a direct target of miR145. miR145 mimics markedly downregulated the expression of ANGPT2 and NFκB p65, boosted the percentage of the CD34+ phenotype, and promoted proliferation and suppressed apoptosis of RAECs under hyperglycemia.Conclusion: miR145 might regulate the viability of RAECs via targeting ANGPT2 and involving NFκB signaling to exert a protective effect on diabetic vasculature.Keywords: diabetic vasculopathy, miR145, angiopoietin 2, ANGPT2, rat aortic endothelial cells, RAECs, hyperglycemia